Design and Development of a Restaurant Information System for Stasiun Jajanan - Agus Ganda Permana; Dewi Safitriani; Devit Setiono (Politeknik Pertanian Negeri Samarinda, 2026)
The rapid advancement of information technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt digital solutions to improve business performance and customer service. Stasiun Jajanan is a culinary MSME that offers various fast-food products, including kebabs, burgers, fried tapioca fritters, Indonesian fried tofu meatballs, and beverages. Promotional activities, order processing, and transaction recording are still conducted manually, resulting in limited promotional reach, inefficient data management, and potential recording errors. This study aims to design and develop a web-based restaurant information system to support business promotion, online ordering, and transaction management for Stasiun Jajanan. The system was developed using the System Development Life Cycle (SDLC) with the Waterfall model, consisting of requirement analysis, system design, development, and testing. Unified Modeling Language (UML) was utilized to model the system through use case, activity, sequence, and class diagrams. The developed system provides several features, including menu management, online ordering, payment processing, transaction management, business information services, and WhatsApp integration for customer communication. System testing was conducted using the Black Box Testing method to verify that all functionalities operated according to the specified requirements. The testing results indicate that the developed system successfully supports menu management, customer ordering, payment processing, and transaction recording. The system improves service efficiency, reduces manual recording errors, and provides customers with easier access to product information and ordering services. The proposed system can therefore support the digital transformation and business growth of culinary MSMEs.